UJI EFEKTIVITAS FUNGISIDA NABATI SEBAGAI BAHAN PENGAWET UNTUK MENCEGAH SERANGAN JAMUR PEWARNA KAYU - Kusumaningsih, Karti Rahayu (Fakultas Kehutanan Institut Pertanian STIPER Yogyakarta, 2021)
Woods which have low natural durability are easy to be attacked with wood staining fungi (blue stain) so can decrease its wood quality. Syzygium aromaticum, Melia azedarach and Piper betle contain of active components (botanical fungicide) that can be used as natural preservative to prevent staining fungi attack. The purpose of this research is to know effect of botanical fungicide species and preserved wood investigated, i.e Paraserianthes falcataria and Toona sureni on the attack intensity of wood staining fungi. Results of the research showed that interaction between botanical fungicide and wood species gived very significant effect on the attack intensity of wood staining fungi. The lowest of attack intensity was resulted on Toona sureni that had preserved by Melia azedarach leaf extract. The leaf extract of Syzygium aromaticum, Melia azedarach and Piper betle could keep Paraserianthes falcataria and Toona sureni wood against staining fungi. Toona sureni wood was more resist against wood staining fungi than Paraserianthes falcataria, it was due to higher extractive in Toona sureni than Paraserianthes falcataria. To preserve woods which had bright colour such as Paraserianthes falcataria, more suitable to use Melia azedarach leaf extract which not change wood colour. Key words: Botanical Fungicide, Preservative, Wood Staining Fungi